Perimenopausal and Postmenopausal Health - Jackevicius Cynthia; Kapral Moira; Chaudhry Ruhee; Cheung Angela M; Robinson Gail (BMC, 2004)
Abstract Health Issue The average age of natural menopause in Western societies is estimated to be 51 years; women in Canada can therefore expect to live, on average, a third of their lives in post-menopausal years. During these years women are at increased risk of chronic diseases such as osteoporosis and cardiovascular disease. Key Findings Clinical and epidemiological data on women in perimenopause are limited. There are no adequate Canadian data on symptom severity and prevalence among perimenopausal and postmenopausal women. Scientific evidence is lacking to support or refute claims that commonly used botanical products can offer therapeutic relief of menopausal symptoms. Recent data from the Women's Health Initiative suggest that combined estrogen plus therapy increases the risk of stroke, coronary artery disease and breast cancer. Hormone therapy is no longer recommended for the prevention of chronic diseases for asymptomatic women. Stroke is an important issue for perimenopausal and postmenopausal women and sex differences may exist in the progestin treatment of stroke. Osteoporosis affects an estimated one in six women over the age of 50. Data Gaps and Recommendations There is a need to conduct clinical and epidemiological research aimed at better understanding the menopausal transition and defining its clinical phases. Investigations aimed at alternative combinations and doses of hormone therapy and non-pharmaceutical alternatives in light of known risks and benefits are also necessary. Health care practitioners and women need to be educated on the risks and effective treatment related to cardiovascular disease so they can present for treatment more quickly and receive the most effective therapies.